Let's Go Public! Taking a Spoken Dialog System to the Real World - Raux, Antoine; Langner, Brian; Bohus, Dan; Black, Alan W; Eskenazi, Maxine (9th European Conference on Speech Communication and Technology, Lisbon, Portugal, 2005)
In this paper, we describe how a research spoken dialog system was made available to the general public. The Let’s Go Public spoken dialog system provides bus schedule information to the Pittsburgh population during off-peak times. This paper describes the changes necessary to make the system usable for the general public and presents analysis of the calls and strategies we have used to ensure high performance.